The current and future burden of heart failure in Portugal - Gouveia, Miguel (2019)
© 2019 The Authors. ESC Heart Failure published by John Wiley & Sons Ltd on behalf of the European Society of Cardiology. ESC HEART FAILURE ESC Heart Failure (2019) Published online in Wiley Online Library (wileyonlinelibrary.com) DOI: 10.1002/ehf2.12399 This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.